Respuesta :

Answer:

Step-by-step explanation:

since the first equation is already simplifies to y = 2x plug in 2x for the y in the second equation and solve

x = -(2x) + 6

x = -2x + 6

3x = 6

x = 2

plug in our x to the original equation

y = 2(2)

y = 4

so our answer is (2,4)

hope this helps <3

Answer:

x = 2

Step-by-step explanation:

If y is 2x, and x is -y + 6, what's x?

So let's use substitution method. Just replace the -y in x = -y + 6 with 2x:

x = -y + 6

x = -2x + 6

add 2x to both sides

3x = 6

divide by 3

x = 2